2016
DOI: 10.1002/chem.201504545
|View full text |Cite
|
Sign up to set email alerts
|

A Boron‐Fluorinated Tris(pyrazolyl)borate Ligand (FTp*) and Its Mono‐ and Dinuclear Copper Complexes [Cu(FTp*)2] and [Cu2(FTp*)2]: Synthesis, Structures, and DFT Calculations

Abstract: Reaction of [Si(3,5-Me2 pz)4 ] (1) with [Cu(MeCN)4 ][BF4 ] (2) gave the mono- and dinuclear copper complexes [Cu2 ((F) Tp*)2 ] (3) and [Cu((F) Tp*)2 ] (4). Both complexes contain the so-far unprecedented boron-fluorinated (F) Tp* ligand ([FB(3,5-Me2 pz)3 ](-) with pz=pyrazolyl) originating from 1, acting as a pyrazolyl transfer reagent, and the [BF4 ](-) counter anion of 2, serving as the source of the {BF} entity. The solid-state structures as well as the NMR and EPR spectroscopic characteristics of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 84 publications
1
2
0
1
Order By: Relevance
“…Also, heteroaromatic substrates were tolerated (entries 16,17) and even highere nantioselectivities could be attained than with the first-generation protocol. With enals like trans-cinnamaldehyde or -crotonaldehyde as imilar efficiency was found for both protocols (entries [18][19][20][21].F or crotonaldehyde we demonstrated that ah ighc atalytic efficiency is maintained with reduced catalyst loadings. For instance, with a reduced catalystl oading of 0.1 mol %ayield of 81 %a nd 94 % ee wasobtained (entry 21).…”
Section: Development Of Asynthetic Protocol With Kcn As the Sole Cyansupporting
confidence: 58%
See 1 more Smart Citation
“…Also, heteroaromatic substrates were tolerated (entries 16,17) and even highere nantioselectivities could be attained than with the first-generation protocol. With enals like trans-cinnamaldehyde or -crotonaldehyde as imilar efficiency was found for both protocols (entries [18][19][20][21].F or crotonaldehyde we demonstrated that ah ighc atalytic efficiency is maintained with reduced catalyst loadings. For instance, with a reduced catalystl oading of 0.1 mol %ayield of 81 %a nd 94 % ee wasobtained (entry 21).…”
Section: Development Of Asynthetic Protocol With Kcn As the Sole Cyansupporting
confidence: 58%
“…PGSE (Pulsed Gradient Spin Echo) NMR experiments performed on both {Al 2 F 3 } and {Al‐F}OTf indicate that {Al 2 F 3 } retains (almost entirely) a dimeric structure in CHCl 3 , whereas {Al‐F}OTf is monomeric (the Supporting Information contains the details and results of the NMR experiments).…”
Section: Resultsmentioning
confidence: 99%
“…Cleavage of BF 4 – to form fluoride ions in the presence of transition metals has been reported, although it is a rare observation and only occurs only in systems with strong N - heterocyclic ligands such as pyridines, pyrazoles, and imidazoles. The decomposition is thought to be the result of F coordination of BF 4 – to a coordinately unsaturated metal center (ML n ) followed by B–F bond cleavage to yield a [ML n –1 F] − complex and a L·BF 3 adduct .…”
Section: Resultsmentioning
confidence: 99%
“…Eine Rçntgenstruktur-analyse (Abbildung 1, rechts) sowie PGSE-NMR-Experimente ("pulsed gradient spin echo"; siehe die Hintergrundinformationen) bestätigen eine monomere Struktur der {Al-F}X-Komplexe. [17] {Al-F}OTf lieferte 3a in quantitativer Ausbeute und mit gutem ee (Nr. 11).…”
unclassified